Mobilizing relief management : towards a framework in location based applications - MA. KRISTINA, SANTOS (Archīum Ateneo, 2010)
Conventional media like radio and television has long been utilized to disseminate up-to-date and real-time information to citizens, particularly in times of disasters. However, there are situations where conventional media are not available. Amidst of th